2015
DOI: 10.1111/bij.12626
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and lineage-specific patterns of genetic diversity and molecular evolution in a group of North American skinks

Abstract: Geography influences the evolutionary trajectory of species by mediating opportunities for hybridization, gene flow, demographic shifts and adaptation. We sought to understand how geography and introgression can generate species‐specific patterns of genetic diversity by examining phylogeographical relationships in the North American skink species Plestiodon multivirgatus and P. tetragrammus (Squamata: Scincidae). Using a multilocus dataset (three mitochondrial genes, four nuclear genes; a total of 3455 bp) we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
(101 reference statements)
2
6
0
Order By: Relevance
“…The range and demographic expansion patterns we observed in T. gracilis largely conform to the predominant phylogeographical pattern observed for vertebrates in central North America (Burbrink et al, 2016), including other snakes (Cox & Chippindale, 2014;McKelvy & Burbrink, 2017), lizards (Moseley et al, 2015), amphibians (Lemmon et al, 2007;Fontenot et al, 2011;Streicher et al, 2012), birds (Ball et al, 1988;Bouzat et al, 1998;Johnson, 2008) and mammals (Riddle & Honeycutt, 1990;Demastes et al, 2002). This shared pattern among diverse taxonomic groups suggests that many terrestrial taxa in this region have recently expanded northwards across the Great Plains, and many have a resulting legacy of depleted genetic variation in the northern segments of their distributions.…”
Section: Range Expansion and Historical Demographysupporting
confidence: 73%
See 4 more Smart Citations
“…The range and demographic expansion patterns we observed in T. gracilis largely conform to the predominant phylogeographical pattern observed for vertebrates in central North America (Burbrink et al, 2016), including other snakes (Cox & Chippindale, 2014;McKelvy & Burbrink, 2017), lizards (Moseley et al, 2015), amphibians (Lemmon et al, 2007;Fontenot et al, 2011;Streicher et al, 2012), birds (Ball et al, 1988;Bouzat et al, 1998;Johnson, 2008) and mammals (Riddle & Honeycutt, 1990;Demastes et al, 2002). This shared pattern among diverse taxonomic groups suggests that many terrestrial taxa in this region have recently expanded northwards across the Great Plains, and many have a resulting legacy of depleted genetic variation in the northern segments of their distributions.…”
Section: Range Expansion and Historical Demographysupporting
confidence: 73%
“…We found that only a subset of mitochondrial and nuclear variation in T. gracilis is present across the large northern swathe of their geographical range, and this is a pattern that has been found in many other taxa (e.g. Fontenot et al, 2011;Streicher et al, 2012;Moseley et al, 2015). The historical contingencies of range expansion and contraction have perhaps increased the potential of southern populations for adaptation to natural and human-mediated alterations in climate and habitat in the terrestrial fauna of central North America.…”
Section: Range Expansion and Historical Demographysupporting
confidence: 49%
See 3 more Smart Citations